Contract of sale: can parties terminate the contract due to movement control order? / Muhammad Asyraf Azni and Suria Fadhillah Md Pauzi - Azni, Muhammad Asyraf; Md Pauzi, Suria Fadhillah (Universiti Teknologi MARA, 2021)
Covid-19 pandemic has caused the government of Malaysia to declare Movement Control Order (MCO). Due to the MCO, some contracts of sale were interrupted and this has caused legal issues on whether the parties can terminate the contracts to avoid further losses. The researchers examine how doctrine of frustration and force majeure can be applied in these contracts. This paper studies various law cases from jurisdictions like Malaysia, Singapore, and the United Kingdom and/or their legal provisions. The researchers discover that contract of sale most likely cannot be terminated by using the force majeure clause, if the contract has one. If the contract does not have the force majeure clause, parties may still rely on doctrine of frustration in order to terminate the contract. The court, nonetheless, will decide based on what the parties have agreed. In conclusion, it is safe for all contracts of sales to include a force majeure clause to better protect both parties from any unforeseen circumstances.